Formulation, tribological performance, and characterization of base oil with ZnO, graphene, and ZnO/graphene nanoparticles additives. Issue 11 (10th November 2020) - Alghani, W.; Karim, M.S.A.; Bagheri, S.; Zaharinie, T.; Gulzar, M.
Abstract: This research article investigates carefully the effect of different nanoparticles zinc oxide (ZnO), graphene, and combinations thereof in API base oil group ΙΙ (PBO−GΙΙ). The morphology of zinc oxide and graphene nanomaterials are depicted by transmission electron microscopy. Sonication treatment and dispersion stability investigations are carried out after the preparation of nanoparticles with surfactant (oleic acid) and pure base oil group ΙΙ for certain concentrations. Oil formulations tested by using a four‐ball machine to find out the coefficient of friction (COF), wear scar diameter (WSD), and specific wear rate (SWR) for each sample. Additionally, scarred balls are characterized by using field emission scanning electron microscopes (FE‐SEM), energy‐dispersive x‐ray spectroscopy (EDX/EDS), elements mapping, Raman spectroscopy, and a three‐dimensional surface texture analyzer to study the morphology of sliding balls after the tribological experiments and to confirm the presence of (zinc oxide+graphene) on the machined balls. Surface roughness measurements implemented for identifying surface finish of scarred balls. The experimental results and surface analyses showed that (0.4 wt.% ZnO+0.2 wt.% graphene) nanolubricant has outperformed behavior compared to base oil group ΙΙ due to the formation of tribofilm on the contacting surfaces during sliding motion. Abstract : This study proved the significant performance of dual nanoparticles (zinc oxide+graphene) in improving the tribological characteristics and surface texture due to the formation of a protective film generated from these nanoparticles (zinc oxide+graphene) on the interacted surfaces. The influence of this mixture led to protect the balls' surfaces from severe friction and adhesion wear. Translation abstract: Dieser Forschungsartikel hat die Wirkung verschiedener Nanopartikel aus Zinkoxid (ZnO), Graphen und Kombinationen davon in der API‐Basisölgruppe ΙΙ (PBO‐GΙΙ) als Inhalt. Die Morphologie von Zinkoxid‐ und Graphen‐Nanowerkstoffen wird durch Transmissionselektronenmikroskopie dargestellt. Untersuchungen zur Ultraschallbehandlung und Dispersionsstabilität werden nach der Herstellung von Nanopartikeln mit Tensid (Ölsäure) und reiner Grundölgruppe II für bestimmte Konzentrationen durchgeführt. Ölformulierungen wurden mit einer Vierkugelmaschine getestet, um den Reibungskoeffizienten (COF), den Verschleißnarbendurchmesser (WSD) und die spezifische Verschleißrate (SWR) für jede Probe zu ermitteln. Zusätzlich wurden vernarbte Kugeln durch Verwendung von Feldemissions‐Rasterelektronenmikroskope (FE‐SEM), energiedispersive Röntgenspektroskopie (EDX/EDS), Elementkartierung, Raman‐Spektroskopie und drei‐dimensionale Oberflächenstrukturanalysator charakterisiert, um die Morphologie von Gleitkugeln nach den tribologischen Experimenten zu untersuchen und das Vorhandensein von (Zinkoxid+Graphen) auf den bearbeiteten Kugeln zu bestätigen. Oberflächenrauheitsmessungen dienen zur Identifizierung der Oberflächenbeschaffenheit von vernarbten Kugeln. Die experimentellen Ergebnisse und Oberflächenanalysen zeigten, dass (0, 4 Gew.% ZnO+0, 2 Gew.% Graphen)‐Nanol‐Schmiermittel im Vergleich zu Grundölgruppe II aufgrund der Bildung von Tribofilm auf den berührenden Oberflächen während der Gleitbewegung ein besseres Verhalten aufweist.